Colloquialisms in Press Texts - Maria Wojtak (Półrocznik Językoznawczy Tertium, 2016)
In the article which is based on specialized press material, the author raises the following issues: why is the colloquial style so attractive for journalists? What features and factors of this variety are treated as particularly useful? What are the results of the frequent use of colloquial forms for the processes of transforming the journalistic style and selected press genres? Colloquialisms considered at the textual level gain the communicative attractiveness because they allow utterances to acquire the status of targeted messages, aimed at seeking contact with a fellow human being, and because they facilitate the escape from abstraction towards concrete speaking (or rather writing), close to everyday experience, imagistic and involved. Thanks to appropriate stylization techniques, journalists construe the world in common with the audience and shape a specific vision of this world: 1/ from the point of view of the audience, taking into account their colloquial images and experiences; 2/ in accordance with the audience expectations, i.e. simply, visually and suggestively; 3/ with the (fake) participation of the audience; 4/ through linguistic means known to the audience (colloquial) or the means created with the stylization techniques typical of colloquial utterances.